Determinants of organisational commitment amongst knowledge workers - Lisa Kinnear; Margaret Sutherland (South African Journal of Business Management, 2000)
The knowledge economy and the knowledge worker are a phenomena of the twentieth century. While knowledge-based organisations are reliant on the knowledge of individuals for their success, they can no longer rely on the loyalty of these highly skilled and marketable employees. The main purpose of this study was to gain insight into what determines commitment to an organisation amongst knowledge workers. The data was collected by means of a survey of 104 knowledge workers from the financial services, information technology and science and technology sectors. The data was subjected to inferential and multivariate statistical analysis. The main findings of this research was that knowledge workers reject traditional retention systems in favour of individualism, independence and personal achievement. These findings are integrated into a model which highlights how knowledge workers' needs can be met through retention strategies which focus on freedom to act independently; financial reward and recognition; developmental opportunities; and access to leading edge technology.
Keywords: 650